Cyclic Orbit Codes with the Normalizer of a Singer Subgroup - F. Bardestani; A. Iranmanesh (Journal of Sciences, Islamic Republic of Iran)
An algebraic construction for constant dimension subspace codes is called orbit code. It arises as the orbits under the action of a subgroup of the general linear group on subspaces in an ambient space. In particular orbit codes of a Singer subgroup of the general linear group has investigated recently. In this paper, we consider the normalizer of a Singer subgroup of the general linear group and its orbit codes. Several properties of these codes are considered.